Analisis Tindak Tutur Ilokusi dalam Video “Merdeka Belajar” pada Kanal Youtube KEMENDIKBUD RI - Ayu Febri Anitasari; Alifah Hasna Salsabila; Icca Dyaz Marshanda; Mukhamad Dwi Prasetyo; Yayang Vintoko; Asep Purwo Yudi Utomo; Rizqi Amalia Dwi Asih (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The research focuses on analyzing one part of a speech act, especially illocutions. The author analyzes how illocutions are used in a certain context in the video "Merdeka Belajar" on the Indonesian Ministry of Education and Culture's YouTube channel. The research aims to analyze the use of illocutionary speech acts in the video "Merdeka Belajar" on the Indonesian Ministry of Education and Culture's YouTube channel, with a focus on the illocutionary theory developed by J. L. Austin, which includes five main forms; representative (assertive), commissive, directive, expressive, and declarative. Research was conducted to better understand how messages and communication are conveyed in the context of the video. This research combines methodological and theoretical approaches. From a methodological aspect, the research applies qualitative methods with descriptive analysis. Theoretically, research is related to the field of pragmatics. The type of research used is a pragmatic study that uses qualitative descriptive methods which include examining documents, listening, and taking notes as data collection tools. The technique for collecting data was carried out using SBLC techniques and recording. Apart from that, the research also used the distribution and matching method for data analysis. This research is useful for knowing how to classify speech acts and increasing knowledge in the field of pragmatics, especially in illocutionary speech acts. In the results of data analysis, 41 data were found from various types of illocutionary speech acts. The number of data for each speech act, namely assertive, is 22 data, directive 7 data, declarative 2 data, commissive 1 data, and expressive 9 data. Based on the research results, the variety of speech acts that are often used in speech on the Indonesian Ministry of Education and Culture's YouTube channel videos are assertive speech acts. The assertive speech acts that appear in the video are statements stating, opinions, showing, reporting, speculating, mentioning, and asserting.